2015
DOI: 10.1161/circinterventions.114.002293
|View full text |Cite
|
Sign up to set email alerts
|

Neuromatous Regeneration as a Nerve Response After Catheter-Based Renal Denervation Therapy in a Large Animal Model

Abstract: T hirteen percent of global mortality has been associated with arterial hypertension. Approximately 34% of the total adult population worldwide is hypertensive, and 13% of this segment of the population is further categorized as having resistant hypertension (RHTN).1 Criteria for the diagnosis of RHTN are the following: any patient requiring ≥3 antihypertensive drugs, including a diuretic, and still maintaining a blood pressure (BP) >140/90 mm Hg.2 RHTN has been previously described as a multifactorial phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…This negative correlation offers some surrogate histological endpoints as assurance that an effective physiologic disconnection is established. Concordant with existing studies, 14 the immunohistochemistry results in our study showed that ablated nerves display decreased staining for tyrosine hydroxylase (TH) and S100 at 7 and 30 days, with some partial recovery of TH staining at 90 days. The regenerative activity was evidenced by the presence of GAP43 at all time points.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This negative correlation offers some surrogate histological endpoints as assurance that an effective physiologic disconnection is established. Concordant with existing studies, 14 the immunohistochemistry results in our study showed that ablated nerves display decreased staining for tyrosine hydroxylase (TH) and S100 at 7 and 30 days, with some partial recovery of TH staining at 90 days. The regenerative activity was evidenced by the presence of GAP43 at all time points.…”
Section: Discussionsupporting
confidence: 92%
“…[21][22][23] This study strongly suggests that renal sympathetic nerves attempt to regenerate but without apparent functional reconnection based on persistent NE level suppression. 14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A catheter provided radial access to minimize vascular complications as well as femoral access. The safety and efficacy of the system were validated by the preclinical animal studies [11][12][13]. This system obtained CE approval in March 2013.…”
Section: Methodsmentioning
confidence: 99%